Establishing Time Limits for Investigations Based on Legal Certainty Values - Hastika, Adrian Richkiel; Erliyani, Rahmida; Suprapto, Suprapto; Zulaeha, Mulyani (Dinasti Research, 2025)
This article examines the reformulation of the investigation time limit regulation based on the value of legal certainty in the Indonesian criminal law system. The provisions in the current Criminal Procedure Code (KUHAP) do not regulate the investigation time limit, thus creating legal uncertainty, weak oversight, and the potential for abuse of authority by law enforcement officers. This study uses a normative juridical approach with descriptive analysis to find the ideal concept for reforming criminal procedure law. The results show that the unclear investigation time limit contradicts the principle of due process of law and the principle of speedy, simple, and low-cost justice. Therefore, a reformulation of the KUHAP is needed by adding provisions regarding the maximum 30-day investigation period, reasons for termination of investigation, and internal and external oversight mechanisms. This reformulation is expected to ensure legal certainty, prevent abuse of authority, and strengthen human rights protection in the criminal justice process in Indonesia.